2015
DOI: 10.1002/bab.1383
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of asparagine synthetase by RNAi suppresses cell growth in human melanoma cells and epidermoid carcinoma cells

Abstract: Melanoma, the most aggressive form of skin cancer, causes more than 40,000 deaths each year worldwide. And epidermoid carcinoma is another major form of skin cancer, which could be studied together with melanoma in several aspects. Asparagine synthetase (ASNS) gene encodes an enzyme that catalyzes the glutamine- and ATP-dependent conversion of aspartic acid to asparagine, and its expression is associated with the chemotherapy resistance and prognosis in several human cancers. The present study aims to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 22 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Depletion of functional ASNS in both mouse and human RMS cells reduced the proportion of cells in S phase and impeded synthesis of nascent polypetide chains. Similarly, ASNS silencing in melanoma cells was recently reported to result in cell cycle arrest ( Li et al, 2015 ). The effects of ASNS reduction in sarcoma cells were reversed by exogenous supplementation with asparagine, supporting the notion that rapidly growing sarcoma cells depend on adequate availability of intrinsic or extrinsic asparagine to support tumor growth.…”
Section: Discussionmentioning
confidence: 84%
“…Depletion of functional ASNS in both mouse and human RMS cells reduced the proportion of cells in S phase and impeded synthesis of nascent polypetide chains. Similarly, ASNS silencing in melanoma cells was recently reported to result in cell cycle arrest ( Li et al, 2015 ). The effects of ASNS reduction in sarcoma cells were reversed by exogenous supplementation with asparagine, supporting the notion that rapidly growing sarcoma cells depend on adequate availability of intrinsic or extrinsic asparagine to support tumor growth.…”
Section: Discussionmentioning
confidence: 84%
“…It could increase tumor growth in vivo , inducing expression of genes associated with metastasis and cancer stem cells 20 22 . ASNS (asparagine synthetase, ASNS) gene encodes an enzyme that catalyzes glutamine- and ATP-dependent conversion of aspartic acid to asparagine, and its expression is associated with chemotherapy resistance and prognosis in several human cancers 23 25 . CXCR1 is a member of the G-protein-coupled receptor family and functions as a receptor for interleukin 8.…”
Section: Discussionmentioning
confidence: 99%
“…ASNS mRNA is significantly overexpressed in human gastric cancer samples compared with normal gastric tissue, and its expression inversely correlates with patient survival (50). ASNS knockdown hinders growth of melanoma cells and epidermoid carcinoma cells, inducing cell cycle, down-regulation of CDK4, CDK6, and Cyclin D1, and induction of p21 WAF (56). With a similar approach, Xu et al reported a role for ASNS in the growth and colony formation ability of lung cancer (NSCLC) cells and demonstrated higher ASNS expression in lung cancer tissues than in normal lung tissue (57).…”
Section: High Asns Expression In Cancer: a Pro-tumor Enzyme?mentioning
confidence: 99%